Pengaruh Latihan Fleksibilitas Statis Terhadap Peningkatan Range Of Motion Sendi Pada Wanita Lanjut Usia - Purnamasari, Agus Dwi, Yulisna Mutia Sari, SST.FT.,M.Sec (GRS) (2016)
The flexibility joints common in the process of aging, thus can reduce movement joints. The decline in their could reduce musculoskeletal range of motion ( ROM ) so as to affect elderly in activity the day to day .Exercise flexibility static done periodically hope can increase to ROM. Research aim is to know the influence of flexibility static on increased ROM in elderly posyandu Nedyo Waras sane and posyandu ngudi waras of jebres The kind of research was research quantitative. Design research uses a quasi experiment design and post pre test with control group design .The samples were 40 elderly with 20 elderly use practice flexibility and 20 as control group. Instrument data use flexibility exercise and measurement ROM with joint movement. analysis data use paired sample test. Results of wilcoxon Test from treatment group obtained p-value = 0.001 . results ot wilcoxon Test frim control group obtained value p = 0.001 . The results of the different influence by Mann Whitney test with p = 0.05 at for shoulder sagittal right , shoulder sagittal left , sagittal right wrist , and ankle . Conclusion: there was influence of exercise flexibility static on increased ROM) in women aged the treatment group in motion joints sholder sagittal right , sholder sagittal left , sagittal right wrist , and angkl . There was a difference in flexibility static the control group in motion joints sholder sagittal right , elbow sagittal , wrist sagittal , sagitaal knee, cervical sagittal , rotation and lumbar region . there was an influence of exercise flexibility static on increased range of motion in women aged the posyandu elderly nedyo sane and posyandu elderly ngudi sane kecamatan jebres. .